Implementasi Desain Promosi Pada Produk Kalbe Konsumer Health - Sarah Anarahma; Ricky Widyananda Putra; Jeanie Annissa (CV. Multi Kreasi Media, 2023)
Promotion is a communication activity that aims to describe some information and persuade that the products or services offered can attract the attention of consumers and can introduce them and increase sales. The purpose of promotion is to change consumer behavior by giving a good impression of the products offered. In the process of making this promotion, the role of a designer is needed in designing designs for the needs of posters, banners, displays, and other design needs. With design, the promotion process to persuade, sell and communicate services and goods will be more easily accepted and seen by consumers through visual forms. The more general the visual design information is, the more important its development status will be. The Digital Marketing Commercial Division of the Jakarta regional Kalbe Consumer Health is the place to carry out tridharma in implementing designs for existing products. The problem encountered in the Digital Marketing Commercial Division of the Jakarta regional Kalbe Consumer Health is that the form of promotional media for their products is not maximal and to increase Brand Awareness. The method used for this community service activity is surveys or interviews and observations made to the Digital Marketing Commercial Division of the Kalbe Consumer Health regional Jakarta, which will be the target of implementing the community service program, to find out the material needs needed